"Hello, Selamat Datang!" A preliminary proposed model of Tourism interpersonal communication from an Islamic perspective amongst frontliners - Nurul Nadirah Abu Hasan; Muhammad Raqib Mohd Sofian; Afiqah Mior Kamarulbaid; Izwan Harith Md. Ithnan (USIM Press, 2024)
These articles explore interpersonal communication in the tourism industry. As the industry faced changes post-pandemic, there is a great reason for the industry to refine people inside the industry, especially the frontliners. Since the frontliners are the first people met and greeted by the tourist, the responsibilities of these groups of industrial players are indeed higher than others. Pieces of the literature suggest that tourism service providers must have expressive communication skills to give a superior product and create a pleasant experience for tourists. Hence, tourism frontliners are expected to be able to express effective interpersonal communication skills both internal and external communication. Interpersonal communication skills in dealing with people are one of the major demands in the industry nowadays. This has created a skills gap in the hospitality industry, which must be addressed if businesses are to remain competitive. It is suggested that the staff in tourism and hospitality should be carefully recruited and should undergo continual training because their communication skills are a significant indicator of their ability to foster favorable interactions with clients. Therefore, this conceptual paper aims to suggest an Islamic approach to improve current tourism frontliners interpersonal communications through Islamic-based communications. The need for interpersonal communication skills in the tourism industry is also highlighted in this article. An integrated model of tourism interpersonal communication with Islamic-based communication was proposed at the end of the article. It is hoped that this conceptual paper will be a stepping stone for research in tourism communication from an Islamic view.